Effect modification of perinatal exposure to air pollution and childhood asthma incidence. Issue 3 (1st March 2018) - Lavigne, Éric; Bélair, Marc-André; Rodriguez Duque, Daniel; Do, Minh T.; Stieb, David M.; Hystad, Perry; van Donkelaar, Aaron; Martin, Randall V.; Crouse, Daniel L.; Crighton, Eric; Chen, Hong; Burnett, Richard T.; et al.
Perinatal exposure to ambient air pollution has been associated with childhood asthma incidence; however, less is known regarding the potential effect modifiers in this association. We examined whether maternal and infant characteristics modified the association between perinatal exposure to air pollution and development of childhood asthma. 761 172 births occurring between 2006 and 2012 were identified in the province of Ontario, Canada. Associations between exposure to ambient air pollutants and childhood asthma incidence (up to age 6 years) were estimated using Cox regression models. 110 981 children with asthma were identified. In models adjusted for postnatal exposures, second-trimester exposures to particulate matter with a 50% cut-off aerodynamic diameter ≤2.5 μm (hazard ratio (HR) per interquartile range (IQR) increase 1.07, 95% CI 1.06–1.09) and nitrogen dioxide (HR per IQR increase 1.06, 95% CI 1.03–1.08) were associated with childhood asthma development. Enhanced impacts were found among children born to mothers with asthma, who smoked during pregnancy or lived in urban areas during pregnancy, males and children born preterm or of low birthweight. Prenatal exposure to air pollution may have a differential impact on the risk of asthma development, according to maternal and infant characteristics. Maternal asthma enhances the effect of air pollution during pregnancy on the risk of developing asthma in children http://ow.ly/eeWp30hSsIb